2002
DOI: 10.1093/clipsy.9.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Let's face facts: Common factors are more potent than specific therapy ingredients.

Abstract: Luborsky et al.'s findings of a non‐significant effect size between the outcome of different therapies reinforces earlier meta‐analyses demonstrating equivalence of bonafide treatments. Such results cast doubt on the power of the medical model of psychotherapy, which posits specific treatment effects for patients with specific diagnoses. Furthermore, studies of other features of this model—such as component (dismantling) approaches, adherence to a manual, or theoretically relevant interaction effects—have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
196
0
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(211 citation statements)
references
References 22 publications
6
196
0
9
Order By: Relevance
“…If this finding is indeed accurate and replicable, it provides support for the argument that "good therapy is good therapy," regardless of the therapeutic model one works within. This common factors approach has been much vaunted in certain parts of the literature on therapeutic outcomes and efficacy research (Messer and Wampold, 2002), however the current study also appears to support the dodo bird verdict in terms of psychotherapy process.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…If this finding is indeed accurate and replicable, it provides support for the argument that "good therapy is good therapy," regardless of the therapeutic model one works within. This common factors approach has been much vaunted in certain parts of the literature on therapeutic outcomes and efficacy research (Messer and Wampold, 2002), however the current study also appears to support the dodo bird verdict in terms of psychotherapy process.…”
Section: Discussionsupporting
confidence: 54%
“…Essentially the question is, "Are clients who are treated with different therapies (which are purported to be so unique from each other) actually manifesting differences in their therapeutic progression?" The controversy centers on a conclusion which has been dubbed the dodo bird verdict (Messer & Wampold, 2002) and states that all psychotherapy outcome rates are similar; there is little difference between the various forms of psychotherapy since they all seem to have virtually the same level of effect as supported by meta-analytic findings. A number of researchers have criticized the dodo bird verdict on the basis of meta-analytic approaches obscuring the details of the impact of each technique by reducing them to a single number (an effect size) which tells us little or nothing of the real world impact of these different treatment styles (e.g., Beutler, 2002;Chambless, 2002) Additionally, there has been criticism which has centered on difficulties with the methodology of meta-analysis, specifically that most authors do not perform appropriate moderator or mediator analyses and thus often neglect important third variables that likely exert an impact on the effectiveness of differing types of psychotherapy (Shadish & Sweeney, 1991).…”
Section: Research Findings Regarding the Effectiveness Of Iptmentioning
confidence: 99%
“…These indicate that treatment methods are not fully able to respond to the special needs of different clients. It has been suggested that common factors are considerably more important for the outcome than the treatment methods in both psychotherapy and substance abuse treatment [20][21][22][23][24] . Taking into account the client's personal characteristics in treatment planning and provision is deemed relevant [25,26] .…”
mentioning
confidence: 99%
“…All together these findings converge into the concept of alliance which is surrounded by the more elusive concept of being together -a common factor within psychotherapy largely independent of theory or technique, whose complex importance for therapeutic relationship, process and outcome cannot be overestimated (Norcross & Wampold, 2011;Messer & Wampold, 2002). Binder et al (2009) gave room for patients' own expressions of successful psychotherapy experiences of change.…”
Section: Johanna Roosmentioning
confidence: 71%
“…The few studies concerning this factor found significant differences among therapists with regard to frequency of patient dropout and therapeutic outcome (Blatt, Sanislow III, Zuroff & Pilkonis, 1996;CritsChristoph, Baranackie, Kurcias, Beck, Carroll, Perry, Luborsky, McLellan, Woody, Thompson, Gallagher & Zitrin, 1991;Luborsky, McLellan, Digeur, Woody & Seligman, 1997). Lower rates of dropout are related to more experience, flexibility in relation to treatment manuals which correlates with accommodation to the specific problems of the patients, training and own psychotherapy and this also accounts for the level of psychotherapy outcome (Blatt et.al., 1996;Crits-Christoph et.al., 1991;Greenspan & Mann Kulish, 1985;Luborsky et.al., 1997;Messer & Wampold, 2002;Norcross & Wampold, 2011;Richmond, 1992;Roth & Fonagy, 1996). Therapists using interventions as extensive and early interpretations and confrontations are perceived as unsympathetic and hostile which is a dropout predictor (Crits-Cristoph & Connolly- Gibbons, 2001;Hilsenroth & Cromer, 2007;Norcross & Wampold, 2011).…”
Section: Johanna Roosmentioning
confidence: 99%